2022
DOI: 10.1002/jmv.27692
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of salivary human herpesvirus‐6 and ‐7 shedding in pregnant women

Abstract: Reactivation of Betaherpesvirinae (Human herpesvirus 6A: HHV-6A, -6B, HHV-7) may be associated with mental illness and host fatigue. This study aimed to determine whether viral reactivation, measured by monitoring salivary viral DNA load, can be used to monitor depression in pregnant and postpartum women. Saliva samples were collected from 64 pregnant women at five points of observation periods. The HHV-6-and HHV-7-specific qPCRs were carried out to measure viral DNA load. When HHV-6 DNA was detected in saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In addition, the present result of HHV7 is compatible with Al-Buhtori et al,2011 andLuis et al, 2011 who found HHV-7 in 34% and 66.9% in spontaneous aborted women, respectively. Furthermore, a recent study found HHV-7, only one pregnant woman did not shed viral DNA at all, and most subjects (46/54, 85.2%) shed viral DNA in all five samples (Suzuki. et al,2022).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, the present result of HHV7 is compatible with Al-Buhtori et al,2011 andLuis et al, 2011 who found HHV-7 in 34% and 66.9% in spontaneous aborted women, respectively. Furthermore, a recent study found HHV-7, only one pregnant woman did not shed viral DNA at all, and most subjects (46/54, 85.2%) shed viral DNA in all five samples (Suzuki. et al,2022).…”
Section: Discussionmentioning
confidence: 92%
“…A previous report has tied HHV-7 infection to spontaneous abortion and neonatal hypotonia. Accordingly, to these investigators have attempted to clarify the relationship between HHV-7 infections during pregnancy (Ohashi et al,2002;Caserta et al,2007;Suzuki. et al,2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, the cases of HHV-7 infection and meningitis in adolescents with normal immune function have gradually increased, causing widespread concern in the medical community[ 4 - 6 ]. The purpose of this study was to investigate the pathogenesis, clinical manifestations, diagnostic methods, and therapeutic effects of herpesvirus 7 meningitis in adolescents with normal immune function and to provide a scientific basis for clinical diagnosis and treatment[ 7 ]. At present, the diagnosis of herpesvirus-7 meningitis in adolescents with normal immune function mainly depends on cerebrospinal fluid examination, virus isolation, and serological detection[ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%